Anti-biofilm and virulence factor-reducing activities of essential oils and oil components as a possible option for bacterial infection control - Reichling, Jürgen (Planta medica, 2020)
Pathogenic biofilm-associated bacteria that adhere to biological or nonbiological surfaces are a big challenge to the healthcare and food industries. Antibiotics or disinfectants often fail in an attempt to eliminate biofilms from those surfaces. Based on selected experimental research, this review deals with the potential biofilm-inhibiting, virulence factor-reducing, and biofilm-eradicating activities of essential oils and single essential oil compounds using Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Chromobacterium violaceum as model organisms. In addition, for the bacteria reviewed in this overview, different essential oils and essential oil compounds were reported to be able to modulate the expression of genes that are involved in the formation of autoinducer molecules, biofilms, and virulence factors. The anti-quorum sensing activity of some essential oils and single essential oil compounds was demonstrated using the gram-negative bacterium C. violaceum. Reporter strains of this bacterium produce the violet-colored compound violacein whose synthesis is regulated by quorum sensing autoinducer molecules called acylhomeserinlactones. Of great interest was the discovery that enantiomeric monoterpenes affected the quorum sensing regulation system in different ways. While the (+)-enantiomers of carvone, limonene, and borneol increased violacein formation, their (−)-analogues inhibited violacein production. For the successful eradication of biofilms and the bacteria living inside them, it is absolutely necessary that the lipophilic volatile substances can penetrate into the aqueous channels of biofilms. As shown in recent work, hydrophilic nano-delivery systems encapsulating essential oils/essential oil compounds with antibacterial effects may contribute to overcome this problem.
Gesehen am 18.03.2021